2000
DOI: 10.1074/jbc.m909616199
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Induces Transactivation of Two Different Populations of the Platelet-derived Growth Factor β Receptor

Abstract: Shc⅐PDGF␤-R complex was inhibited by antioxidants such as N-acetylcysteine and Tiron, but not by calcium chelation. However, transactivation of PDGF␤-R by AngII (measured by PDGF␤-R tyrosine phosphorylation) differed significantly from PDGF-BB. Evidence to support different mechanisms of PDGF␤-R phosphorylation includes differences in the time course of PDGF␤-R phosphorylation, differing effects of inhibitors of the endogenous PDGF␤-R tyrosine kinase and Src family tyrosine kinases, differing results when the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
3

Year Published

2001
2001
2006
2006

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 42 publications
4
113
3
Order By: Relevance
“…GPCRs can also activate receptor tyrosine kinases other than EGFR. PDGFR transactivation has been demonstrated in COS-7 cells and vascular smooth muscle (by LPA and angiotensin II, respectively) (Linseman et al, 1995;Herrlich et al, 1998;Heeneman et al, 2000), and IGF1R transactivation was reported in primary rat smooth muscle cells by thrombin stimulation (Rao et al, 1995). Earlier work on the mitogenic response in quiescent murine fibroblasts (Swiss 3T3 cells) demonstrated that certain growth factors can confer a ''complete'' mitogenic response, while others are dependent upon the presence of other factors to activate complementary pathways (Rozengurt, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…GPCRs can also activate receptor tyrosine kinases other than EGFR. PDGFR transactivation has been demonstrated in COS-7 cells and vascular smooth muscle (by LPA and angiotensin II, respectively) (Linseman et al, 1995;Herrlich et al, 1998;Heeneman et al, 2000), and IGF1R transactivation was reported in primary rat smooth muscle cells by thrombin stimulation (Rao et al, 1995). Earlier work on the mitogenic response in quiescent murine fibroblasts (Swiss 3T3 cells) demonstrated that certain growth factors can confer a ''complete'' mitogenic response, while others are dependent upon the presence of other factors to activate complementary pathways (Rozengurt, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Another level of complexity may be associated with interactions with nonchemokine receptors present on the cell surface, by a process known as "transactivation." GPCR-mediated transactivation of the epidermal growth factor [107] and the platelet-derived growth factor receptors [108] have been reported. Given that CCL5-CCR5 activation of Jurkat T cells correlates with the expression of CD3 [19], that CCR5 expression is associated with constitutive CD4 [9] expression and CCR5 localizes to lipid rafts upon ligand binding [4,6], activated CCR5 may function to recruit signaling intermediates of the TCR to potentiate (co)stimulation of T cells.…”
Section: Ccr Cross-talk With the Tcr Signaling Complexmentioning
confidence: 99%
“…In L cells, which lack EGF receptor expression, LPA stimulates phosphorylation of PDGFbR, and LPA-stimulated Shc and ERK1/2 phosphorylation is completely blocked by inhibiting the PDGF receptor (Herrlich et al, 1998). Stimulation of vascular smooth muscle cells with angiotensin II appears to induce phosphorylation of a subpopulation of PDGFbR that are distinct from those activated by direct application of PDGF (Heeneman et al, 2000). As with EGF receptor transactivation, Src activity may be involved both as an upstream mediator of PDGFbR transactivation (Tanimoto et al, 2002), and downstream as an intermediate in PDGF receptormediated mitogenesis (Barone and Courtneidge, 1995).…”
Section: Gpcr-mediated Transactivation Of Receptor Tyrosine Kinasesmentioning
confidence: 99%